A technology acceptance study of online banking service in Malaysia - Paul H. P., Yeow; Y. Y., Yuen (2008)
Online banking service (OBS) is new in Malaysia (introduced about 6 years ago). The study is the first research in Malaysia that investigates user acceptance of OBS based on Unified Theory of Acceptance and Use of Technology model (Venkatesh, Morris, Davis and Davis, 2003). Two hundred and eighty questionnaires were distributed and collected from two major cities, Kuala Lumpur and Melaka. Since this is a preliminary study, only descriptive statistics was used to analyse the data. The results show that Malaysians have intentions of using OBS (mean rating of close to 4.00). Moreover, Malaysians recognize the benefits of OBS by giving a high mean rating (close to 4.00) to performance expectancy. However, they give relative low mean ratings (close to 3.00) on other indicators of Behavioural Intention to Use OBS such as effort expectancy, social influence, facilitating conditions and perceived credibility. Recommendations were given to promote a safe, efficient and conducive environment for user adoption of online banking.